Reseña - Barrios Giraldo, David (Revista Interamericana de Bibliotecología, 2016)
Weld, K. (2014). Paper Cadavers: The Archives of Dictatorship in Guatemala. Durham, North Carolina: Duke University Press. p. 352. ISBN: 978-0-8223-5602-8